In Bruges [videorecording (DVD)] - McDonagh, Martin; Farrell, Colin, 1976-; Gleeson, Brendan; Fiennes, Ralph (Universal Studios Home Video, 2008)
Two hit men, ordered by their ruthless crime boss to hideout in the fairytale city of Bruges (Belgium), soon find themselves in a life and death struggle of comic proportions.